2004
DOI: 10.1111/j.1365-2929.2004.01823.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical students' initial reports of the educational climate in a single medical school

Abstract: Students' transition to the hospital environment was difficult. This may become less of an issue as medical curricula become more integrated. Specific strategies to induct students into the hospital, and increased staff awareness of their needs, could also help. Ensuring an inclusive atmosphere may be more difficult, requiring cultural change.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
124
1
8

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(145 citation statements)
references
References 16 publications
(27 reference statements)
8
124
1
8
Order By: Relevance
“…The results of our study are consistent with earlier findings about the effect of real patients on student learning: the real patient leads to better acquisition and retention of knowledge (Prince et al 2000;Seabrook 2004), motivates learning (Prince et al 2000), vividly demonstrates the impact of disease on patients' lives (Cooper et al 2001;Frank et al 1996), and stimulates the process of professional socialisation (Dornan and Bundy 2004;Pitkala and Mantyranta 2003). However, our study revealed additional effects of preclinical patient contacts on student learning.…”
Section: Conclusion and Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…The results of our study are consistent with earlier findings about the effect of real patients on student learning: the real patient leads to better acquisition and retention of knowledge (Prince et al 2000;Seabrook 2004), motivates learning (Prince et al 2000), vividly demonstrates the impact of disease on patients' lives (Cooper et al 2001;Frank et al 1996), and stimulates the process of professional socialisation (Dornan and Bundy 2004;Pitkala and Mantyranta 2003). However, our study revealed additional effects of preclinical patient contacts on student learning.…”
Section: Conclusion and Discussionsupporting
confidence: 83%
“…A systematic review of early patient contacts cited positive effects on professional socialisation (Dornan et al 2006). Reported positive effects also include improved acquisition and retention of knowledge (Prince et al 2000;Seabrook 2004) and contextualisation of basic science knowledge (O'Brien et al 2001;Mann 1994) by linking real patients with theory. However, no detailed studies have addressed exactly in what way early patient contacts impact on how students acquire knowledge, use basic science knowledge and integrate basic science and clinical knowledge during clinical reasoning.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…While such patterns may reflect the variable individual strengths and attributes of medical students, more research should be done firstly to confirm this phenomenon, but also to understand the factors that contribute to it. Difficulty adapting to new teaching methods and the clinical environment is a known factor associated with difficulties in transition [2], and so any knowledge of student factors associated with better attainment could be clearly communicated to students prior to commencing clinics to enable them to develop effective learning strategies. Moreover, it would also enable institutions and teaching hospitals to adapt teaching methods.…”
mentioning
confidence: 99%